2003
DOI: 10.1103/physrevlett.91.047903
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorics and Quantum Nonlocality

Abstract: We use techniques for lower bounds on communication to derive necessary conditions (in terms of detector efficiency or amount of super-luminal communication) for being able to reproduce the quantum correlations occurring in EPR-type experiments with classical local hidden-variable theories. As an application, we consider n parties sharing a GHZ-type state and show that the amount of superluminal classical communication required to reproduce the correlations is at least n(log 2 n − 3) bits and the maximum detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…These Bell coefficients correspond to the so-called extended parity game considered in Ref. [14]. An equivalent definition, more similar to the definition of the Bell inequality (5) treated in section II is that M αβγ = cos[π(α + β + γ)/m], whenever the absolute value of this expression is one, and M αβγ = 0 otherwise.…”
Section: Bell-type Inequalities Based On the Extended Parity Gamementioning
confidence: 99%
See 1 more Smart Citation
“…These Bell coefficients correspond to the so-called extended parity game considered in Ref. [14]. An equivalent definition, more similar to the definition of the Bell inequality (5) treated in section II is that M αβγ = cos[π(α + β + γ)/m], whenever the absolute value of this expression is one, and M αβγ = 0 otherwise.…”
Section: Bell-type Inequalities Based On the Extended Parity Gamementioning
confidence: 99%
“…This generalization is discussed in section II, whereas another family of Bell inequalities, based on the extended parity game [14], is discussed in section III. Notably, this game exhibits pseudo-telepathy [15], and the corresponding Bell inequality has the same performance (for m a power of 2) as our Bell inequality of section II.…”
Section: Introductionmentioning
confidence: 99%
“…The case k = 2 and arbitrary n was studied by Mermin [19] and recently revisited by Brassard et al [20,21]. In Buhrman et al [12] and our earlier research [15] the case where the number of settings k is a power of two was considered. In [12] it was shown that the amount c of classical communication which the parties must broadcast in order to reproduce exactly the correlations from Definition 10 is c = O(n log n) when k = O(n).…”
Section: Lemmamentioning
confidence: 99%
“…Our result constitutes to our knowledge the first example in which the degree to which the quantum correlations are nonlocal increases with the size of the entangled system in the presence of noise and as such constitute a significant advance in our understanding of quantum communication complexity and of quantum nonlocality. The present work builds upon the earlier results of [12] and [15]. As in these references we rely heavily on techniques and ideas from the field of communication complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation